The variability and dynamics of the Antartic Circumpolar Current south of Africa using proxy techniques - Swart, Sebastiaan (Department of Oceanography, 2023)
The general circulation of the Southern Ocean is dominated by the eastward flowing Antarctic Circumpolar Current (ACC). This is a continuous feature linking the three major ocean basins and thus forms a vital link in the transport of heat and salt on a global scale. These exchanges provide a vital mechanism for the global thermohaline circulation (THC), which regulates the Earth's climate. In the high latitudes, where conditions are hostile, routine hydrographic observations are scarce resulting in a poor understanding of the physical and dynamic processes controlling the variability of the ACC and its influence on the THC. The GoodHope program launched in early 2004 aimed to establish an intensive monitoring platform that would provide detailed information on the physical structure and volume flux of water masses south of Africa. Sustained observations along the GoodHope cruise track provide the means to monitor the vertical structure and variability of the ACC and its associated fronts south of Africa. Such intense monitoring has been under way in the Drake Passage and south of Australia since the 1970s. A major objective of this thesis is to provide sound estimates of ACC transport and variability using both in situ measurements and remote sensing techniques. These estimates are crucial in understanding the role the ACC plays in the global thermohaline circulation (THC) and how the region south of Africa acts as a major conveyor of heat and salt to the higher latitudes. Baroclinic transports of the ACC, relative to 2500 dbar, are calculated from altimetry data alone. These transports agree with simultaneous observed estimates (rms difference in net transport is 5.2 Sv). These observations suggest that sea level anomalies largely reflect baroclinic transport variations above 2500 dbar. The transports contribution per ACC front shows that the SAF is responsible for the highest variability signals (>50%) even though its net transport contribution to the ACC was less (9%) than the APF. Furthermore, direct measurements of heat and salt content in the Southern Ocean are based on the few synoptic transects, the majority of which are restricted in the austral summer. To overcome the poor temporal and spatial resolution of measurements in the south African sector of the Southern Ocean, this thesis makes use of the gravest empirical mode (GEM) method and applies this technique to weekly composites of satellite altimetry data. The GEM method makes use of all available hydrographic casts from the south-east Atlantic Ocean and projects the data into a baroclinic stream function space parameterised by pressure and dynamic height. The GEM fields were shown to compare closely with independent in situ observations of the water column, capturing more than 97% of the total temperature and density variance in the ACC domain. The GEM-derived heat and salt content estimates attempt to determine the variability signals of the ACC due to external influences, such as topographical obstacles and oceanic features originating from subtropical regions. The exploitation of such proxy methods is useful in improving our understanding of the subsurface properties of the Southern Ocean and more importantly the influences temporal changes in the system have on the structure and transport of the ACC. With time, these methods will be refined with the input of new observations, thereby enhancing their ability to determine the dynamic nature of the ACC and its impact on the Earth's system.